Choice in Public Health Services: A Multilevel Analysis of Perceived Primary Care Doctor Choice in 22 Countries. (November 2017) - Van de Walle, Steven; Marien, Sofie
The introduction of choice in public services, and in health services more specifically, is part of a wider movement to introduce consumerism in health care. We analyze how citizens perceive the availability of choice of primary care doctors in 22 European countries and the factors that influence their opinions using multilevel analyses and data from the European Social Survey (Round 2, 2004; 22 countries, N = 33, 375). We distinguish between individual factors and structural or country-level factors. We find that perceptions of having enough choice are not influenced by the opportunity to freely choose primary care doctors, the density of doctors in a country, or the level of health expenditure. Instead, these perceptions are influenced by individual attributes, such as personal health circumstances, age, sex, location of residence (rural or urban), and level of satisfaction with the health system.